Meningkatkan Hasil Belajar Siswa pada Operasi Hitung melalui Pendekatan Matematika Realistik - Jusmanidar Jusmanidar (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2017)
Mathematics learning at 2nd grade students of SDN 21 Batang Anai Kabupaten Padang Pariaman used to run traditionally; did not make connection between learning and real world.  This is a classroom action research aimed to improve students’ learning achievement for number operations by implementing realistic mathematics education (RME). This study consists of two cycles that includes four steps, i.e. planning, implementation, observation, and reflection. Data of this study were obtained through observation, interview, and test. Mean of students’ learning achievement in cycle I is 77.2 and 88.2 in cycle II. Hence, it was concluded that implementation of RME can improve students’ learning achievement, especially for topic of number operations.